The design and safety features of AP1000 - Tan, Peng Yeow (2015)
The purpose of this project is to investigate the design and safety features of the Westinghouse nuclear reactor AP1000 and to determine if it is feasible for Singapore to adopt nuclear energy as an alternative energy source. Today, the world is facing challenging issues with the sustainability and increasing price of fossil fuel. Therefore there is a need to shift the attention to more sustainable and environmental friendly energy sources like nuclear energy. Although nuclear energy can be obtained through nuclear fission and nuclear fusion, nuclear fusion is still not a viable source of energy. Nuclear energy is highly misunderstood as being an expensive and dangerous energy source. However, evidence has shown that actually nuclear fission is safe and technology has allowed it to be an economically competitive energy source. Nuclear reactors can be classified into 4 generations. However, as of today, only generations 2 to 3+, such as AP1000, are in existence while generation 4 reactors have yet to be established. Introducing the AP600 reactor is a generation 3 reactor with simplified design system and aims to improve operations and reduce maintenance training and timing. AP 1000 is a nuclear reactor of Westinghouse and is one of the safest and economically competitive power plants in the world. It allows modules to be built separately and simultaneously which reduces construction cost. It also includes passive safety systems which reduces operator interaction, making it safer for operators. AP1000 is also less complex and smaller in size in comparison with other reactors. Singapore, being heavily reliant on fossil fuels, would be greatly affected by the depleting supply of fossil fuels. Therefore Singapore has to shift to alternative energy sources. Nuclear is one of the possibilities as Singapore has scarce renewable sources like wind and hydro. Singapore could potentially build the reactor underground which serves as a safer siting option as well as compensating for the limited land space in the country.